When Signs are Divergent: Analysing Farmer-Herder Conflicts in Southwest Nigeria Through Biosemiotic Theory - Mahmud, Memunat Olayemi (International Journal of Language and Literary Studies, 2026)
Since Nigeria's return to democracy in 1999, conflicts between predominantly Fulani Muslim herders and largely Christian sedentary farmers have killed thousands and displaced hundreds of thousands more. These confrontations intensified dramatically in Southwest Nigeria during 2020-2021, transforming the historically peaceful Yoruba region into a conflict zone. This paper argues that violence emerges when communities with incompatible meaning-making systems share space without interpretive frameworks enabling mutual intelligibility. Using Uexküll's Umwelt theory and Hoffmeyer's semiotic scaffolding concept, it analyses how different species inhabit distinct perceptual worlds that generate fatal misreadings. Through intensive analysis of four documented conflicts - Igangan (Oyo), Imeko-Afon (Ogun), Jugbere (Ondo), and Ayegbaju-Ekiti - during 2019-2021, the paper demonstrates how cattle, crops, humans, and landscapes constitute an ecology of meaning where each agent produces and interprets signs differently. A central finding is that cattle operate as autonomous agents, following species-specific foraging Umwelten that systematically cause crop destruction regardless of herder intentions, explaining why legal prohibitions and security interventions consistently fail. Findings show that semiotic breakdown interacts with material and political factors to produce violence, suggesting that conflict resolution requires physical infrastructure channelling bovine behaviour and rebuilding shared interpretive frameworks alongside addressing resource claims.